Invasive Aedes albopictus is a competent vector for O'nyong Nyong virus - Jagtap, Swati; Altinli, Mine; Badusche, Marlis; Chevalier, Manuel; Becker, Norbert; Leggewie, Mayke; Schnettler, Esther (One health, 2025)
O'nyong-nyong virus (ONNV) is a zoonotic vector-borne alphavirus with humans as primary hosts during urban outbreaks. While its enzootic transmission cycle is not well investigated, its pattern of disappearance and reemergence suggests overlooked but critical wildlife reservoirs. While ONNV travel-related cases were reported in Canada and Germany, autochthonous transmission is limited to sub-Saharan Africa. The lack of specialised vectors, such as anopheline mosquitoes, is considered to be one of the reasons. Here, we investigated the vector competence of native and invasive culicine mosquitoes from Germany. While the tested native culicine mosquitoes from Germany did not transmit ONNV, our results provide experimental evidence for potential ONNV transmission by invasive Ae. albopictus mosquitoes. We further investigated the role of temperature on ONNV transmission. Ae. albopictus mosquitoes are highly invasive and have become widespread in Europe in the last decade. Our results highlight that, combined with rising summer temperatures and the abundance of competent vectors, ONNV may emerge as a public health threat for Europe in the near future.
Gesehen am 29.10.2025